Faktor Pengaruh Nilai Perusahan pada Perusahaan Transportasi yang terdata di Bursa Efek Indonesia Periode 2015 - 2020 - Rosyid; Daffa Haryasalam (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to prove the effect of firm size, capital structure, and solvency either partially or simultaneously on firm value in the transportation sub-sector listed on the Indonesia Stock Exchange. The period used in this study is 6 years, starting from 2015-2020. This research uses a quantitative approach with an associative approach. And the sampling technique used in this research is the purposive sampling technique. The type of data used in this research is secondary data. So that the sample in this study amounted to 22 companies that are in the Transportation Sub-Sector listed on the Indonesia Stock Exchange in the 2015-2020 period. The data analysis technique used in this research is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that partially firm size has a positive and significant effect on firm value, partially capital structure has a negative and significant effect on firm value, then partially solvency has a positive and significant effect on firm value. The results of the study simultaneously show that firm size, capital structure, and solvency have an effect on firm value